Intermedin is a new angiogenic growth factor - Robert S. Smith; Lin Gao; Grant Bledsoe; Lee Chao; Julie Chao (2009)
Intermedin (IMD) is a newly discovered peptide closely related to adrenomedullin. We recently reported that IMD gene delivery prevented kidney damage and capillary loss in a rat model of chronic renal injury. In this study, we evaluated the role of IMD in angiogenesis in the ischemic hindlimb. Adenovirus containing human IMD or control adenovirus (Ad.Null) was injected into the adductor muscles of rats immediately after femoral artery ligation. The expression of human IMD was detected in the skeletal muscle 5 days after the viral injection. Blood perfusion in the ischemic hindlimb was monitored by laser-Doppler imaging from 1 to 3 wk after gene delivery. When compared with animals receiving Ad.Null, those with IMD gene transfer resulted in a time-dependent increase in blood perfusion. IMD gene delivery also increased capillary and arteriole density in ischemic hindlimb, identified by anti-CD-31 and α-smooth muscle actin immunostaining. Angiogenesis promoted by IMD was confirmed by increased capillary formation and hemoglobin content in Matrigel implants containing IMD peptide in mice. In cultured endothelial cells, IMD induced cell migration and tube formation, and these effects were blocked by the inhibition of extracellular signal-regulated kinase (ERK), Akt, nitric oxide (NO) synthase (NOS), vascular endothelial growth factor receptor-2 (VEGFR-2), and anti-IMD-neutralizing antibody. IMD was found to increase the phosphorylation of ERK, Akt, and endothelial NOS, as well as to augment NO formation, VEGF, and VEGFR-2 synthesis. Taken together, these results indicate that IMD enhances angiogenesis through ERK, Akt/NOS/NO, and VEGF/VEGFR-2 signaling pathways and raises the potential of IMD gene or peptide administration in the modulation of endothelial dysfunction.